PENGARUH KEPEMIMPINAN PARTISIPATIF, LINGKUNGAN KERJA FISIK, KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN DI HOTEL RAMA RESIDENCE - I Made Gede Bagus Pasek Dwipayana; Gusti Ngurah J. Adinegara; I Gusti Bagus R. Utama (LPPM Universitas Dhyana Pura, 2023)
This study aims to determine the effect of participatory leadership, physical work environment and financial compensation on employee performance at the Rama Residence Hotel. The study involved a sample of 39 respondents through non-probability sampling techniques. Data collection was carried out using a Likert scale questionnaire. The data analysis technique uses multiple linear regression. Hypothesis testing using the F test and t test at a significance level of 5%. The results showed that partially participative leadership (X1) had a positive and significant influence on employee job satisfaction (Y) at the Rama Residence Hotel. This can be seen from the regression coefficient b1X1 which is positive at 0.169. This test is supported by a statistical test t (t - test) which states that t count is greater than t table, which means Ha is accepted. Partially the physical work environment (X2) has a positive and significant influence on employee job satisfaction (Y) at the Rama Residence Hotel. This can be seen from the regression coefficient b2X2 which is positive at 0.296. This test is supported by a statistical test t (t - test) which states that t count is greater than t table, which means Ha is accepted. Partially financial compensation (X3) has a positive and significant influence on employee job satisfaction (Y) at the Rama Residence Hotel. This can be seen from the regression coefficient b3X3 which is positive at 0.446. This test is supported by a statistical test t (t - test) which states that t count is greater than t table, which means Ha is accepted. Simultaneously participative leadership, physical work environment, and financial compensation have a positive and significant effect on employee job satisfaction (Y) at the Rama Residence Hotel. This is proven through multiple regression analysis Y = 5.355 + 0.169X1 + 0.296X2 + 0.446X3 Additionally, it is confirmed by the F (F-test) test where the F count is greater than the F table, which means Ho is rejected and Ha is accepted.